State of Play Civil Society Organization in Montara Incident in 2009 - Ridwan Stanley Sinaga; Ika Riswanti Putranti (Jurnal Studi Sosial dan Politik, 2021)
This paper seeks to explain the role of the West Timor Care Foundation (YPTB) in the 2009 Montara dispute using the concept of the Transnational Advocacy Network and the Boomerang Model. This study found that YPTB had a role as an external-pressure and agenda-setter for the Indonesian and Australian governments because it failed to accommodate community problems. Pressure is carried out by means of diplomacy and litigation to overcome government inconsistencies with implication in the bilateral atmosphere of the two governments. YPTB's efforts to influence this policy set in motion the Boomerang Effect as a way to settle the Montara settlement. This research is qualitative studies with purpose to investigate WTCF as an analyze unit and as the informant key. The results of this study contribute to understanding the processes that can mobilize interest groups and the ways in which they resolve disputes. The failure of governments to design interest triggers to use their networks and force changes to cross-border policies.